Reframing Entrepreneurial Education Assessment in Islamic Higher Education: Mapping Global Evidence and Proposing a Learning-Oriented Evaluation Framework - Maulidi, Achmad; Tamami, Badrut; Malyuna, Sita Isna; Kusaeri, Kusaeri; Suparto, Suparto (Jurnal Pendidikan Islam, 2025)
Purpose – This study addresses the critical need for a contextual and comprehensive evaluation system for entrepreneurship education in Islamic Higher Education Institutions (PTKI). While global research increasingly supports the role of entrepreneurship education in driving innovation and sustainability, most existing studies focus on entrepreneurial intentions or self-efficacy, with limited attention to systematic evaluation frameworks. This study aims to map global scientific trends, identify adaptive evaluation models, and formulate a Learning-Oriented Assessment (LOA)-based conceptual framework tailored for PTKI. Design/methods/approach – Using a mixed-methods exploratory design, the study integrates bibliometric analysis of 1,428 Scopus-indexed articles (2015–2025) with a systematic literature review (SLR) of 29 empirically and theoretically grounded studies. Analytical tools such as VOSviewer, R Studio Bibliometrix, and PRISMA 2020 protocols were employed to ensure methodological rigor. The PICOS framework guided article selection and synthesis. Findings – Results show a steady 5.12% annual growth in publications, with hybrid models—particularly the CIPP-AHP-FCE—emerging as the most adaptive across diverse institutional contexts, including those with limited technological capacity. Dual-focused evaluations that integrate both learning processes and outcomes are found to be more holistic and sustainable. However, process-oriented assessment models remain underrepresented in current literature. Research implications – PTKIs can adopt the synthesized models and proposed framework to develop evaluation systems that align with their technological readiness, educator competencies, and spiritual mandates. This supports the advancement of reflective, inclusive, and pedagogically effective entrepreneurship education.